COVID-19's Social Ecological Impacts on Health and Human Services Worker Well-being. Issue 3 (3rd April 2022) - Magruder, L.; Wilke, D.; Radey, M.; Cain, M.; Yelick, A.
ABSTRACT: Health and human services workers (HHS; e.g., child welfare, physical and mental healthcare) engage with clients facing heightened vulnerability during the COVID-19 pandemic. Under typical circumstances, HHS workers face a host of challenges in carrying out their job responsibilities such as high caseloads and burnout, and now navigate new challenges such as social distancing protocols and protecting their own health and that of their families and clients. This study explored the experiences of 531 HHS workers in Florida to understand well-being impacts of COVID-19 on the HHS workforce. Using a social ecological framework, we analyzed open-ended responses from HHS workers to better understand the multi-level and frequently intertwined impacts of COVID-19. Participants reported numerous proximal factors (i.e., intrapersonal, interpersonal, organizational) impacting their well-being but fewer distal factors (i.e., community, public policy). Agencies should work to understand the intersecting vulnerabilities of their workers and implement safety protocols to preserve workers' well-being.